Realtà in registrazione. Ontologia e riproducibilità tecnica della memoria - Pezzano, Giacomo (Mechane, 2020)
The paper discusses the metaphysics of the web proposed by M. Ferraris recently, considered as one of the possible ontologies of the ICT. It starts clarifying two Ferraris’s key-ideas: i) ICT are technologies of the memory and information is linked to ethos (action) and not eidos (knowledge); ii) the socio-technical revolution of the web eveals the intimate structure of reality as such (§ 1). Thus, the foundations of Ferraris’s realism of the hysteresis are sketched (§ 2), highlighting that it is a realism of recording which wants to be at the same time speculative and ordinary (§ 3), and that it nevertheless entails an ontology based not on the object, but on the trace (§ 4). Finally, the focus goes on the question of the revision of our ordinary image of reality, based on thinghood, stressing that tools such as Extended Reality and phenotechnology could open to a different way not only of conceiving reality, but also of perceiving it (§ 5).